Panoramas da Serra do Espinhaço: um ensaio de mapeamento fotográfico da paisagem - Paulo Baptista (2010)
This thesis presents concepts that relate the production and usage of landscape images to the ways we perceive, interpret and interact with the physical environment in which we live. As a theoretical background to our statements we refer basically to authors that explore the theme of the landscape from the viewpoints of art history, photography and the earth sciences. We also experiment a practical model for producing landscape photographs that combines aesthetical and technical or informative content as an attempt to strengthen the relations between artistic creation and scientific interpretation processes. This model employs very high-resolution digital photography equipment and methods, as well as computer-based geocoding of the resulting images.